Evaluating daily physical activity and biomechanical measures using wearable technology in people with Achilles tendinopathy: A descriptive exploratory study. (April 2022) - Tavakkoli Oskouei, Sanam; Malliaras, Peter; Hill, Keith D.; Clark, Ross; Perraton, Luke
Abstract: Background: Load management is considered an important factor for prevention and treatment of Achilles tendinopathy. However, little attention has been given to monitoring daily load objectively in this population. Objectives: We aimed to explore patterns in proxies of daily load derived from a six-axis inertial measurement unit (IMU) over a one-week period and the concordance between day-to-day fluctuation in pain intensity and IMU measures. Design: Descriptive exploratory study. Method: Ten participants with Achilles tendinopathy (age: 53.00 ± 12.37) wore an IMU on the affected ankle for one week. Participants were contacted via text message three times daily to rate their worst pain intensity. Physical activity and biomechanical measures derived from the IMU signals including daily number of steps, peak stride rate, peak shank acceleration, and peak shank angular velocity were calculated. Results: The relationship between weekly worst pain and physical activity levels appeared modest; with increased steps not seeming to be linked to increased or reduced pain levels. According to the daily pain and daily IMU measures, a concordant pattern was evident in younger, highly active participants. However, in the middle-aged/older less active participants, there was either a fluctuation in pain intensity without fluctuation in the IMU measures, or a stable pattern of both pain and IMU measures. Conclusions: Our exploratory study results suggest that continuous monitoring of proxies of daily load measures in parallel with pain may provide information about load management strategies in people with Achilles tendinopathy. Monitoring of these proxies may ultimately have a role in improving Achilles tendinopathy management. Highlights: Load mismanagement during daily activities may interfere with success of exercise programs in Achilles tendinopathy. Use of wearable technology provide information about load management strategies of people with Achilles tendinopathy in daily life. There were variable patterns based on daily load proxies and pain among people with Achilles tendinopathy. Daily load proxies and pain had a concordant pattern in younger highly active participants. Daily load and pain monitoring may help to identify people at risk of load mismanagement.